Blood Serum From Head and Neck Squamous Cell Carcinoma Patients Induces Altered MicroRNA and Target Gene Expression Profile in Treated Cells - Allen, Brittany; Schneider, Augusto; Victoria, Berta; Nunez Lopez, Yury O.; Muller, Mark; Szewczyk, Mateusz; Pazdrowski, Jakub; Majchrzak, Ewa; Barczak, Wojciech; Golusinski, Wojciech; Golusinski, Pawel; Masternak, Michal M. (Frontiers in Oncology, 2018)
The Head and Neck Squamous Cell Carcinomas (HNSCC) represent one of the sixth most common cancer in humans, with close to 600,000 new diagnosis every year worldwide and nearly 350,000 individuals diying. The lack of significant changes oprognosis in HNSCC in over a decade accounts for this low overall survival rate. Better understanding of molecular mechanism in HNSCC carcinogenesis and development of new cell based assays for diagnostics could allow earlier detection, easier follow up and the use of more specific and effective treatments in the future. In this study we investrigated the role of serum from HNSCC patients on the regulation of miRNA expression in exposed cells in vitro. Next-Generation sequencing of miRNA revealed that serum from HNSCC patients induced a different miRNA expression profile than the serum form healthy individuals. Out of 377 miRNA detected we found 16 miRNAs that were differentially expressed when comparing cells exposed to sera from HNSCC or healthy individuals. The analysis of gene ontologies and pathway analysis revealed that these miRNA target genes involved in biological cancer-related processes including cell cycle and apoptosis. The real-time PCR analysis revealed that serum from HNSCC patients downregulate the expression level of 5 genes involved in carcinogenesis and two of these genes, P53 and SLC2A1 are direct targets of detected miRNAs. These novel findings provide new insight into understanding cancer-associated factors in circulation regulating the expression of genes and regulatory elements in distal cells in favor of tumorigenesis with potential for new therapeutic approaches and more specific diagnostics with tumor specific cell lines or single-cell in vitro assays for personalized treatment and early detection of primary tumors or metastasis.